Resistance mechanisms to HER2-targeted therapy in gastroesophageal adenocarcinoma: A systematic review. (July 2022) - Blangé, Dionne; Stroes, Charlotte I.; Derks, Sarah; Bijlsma, Maarten F.; van Laarhoven, Hanneke W.M.
Highlights: Resistance to anti-HER2 therapy in esophagogastric adenocarcinoma hampers efficacy. Different mechanisms of resistance are discussed in this review. HER2 receptor changes and activation of alternative receptors and downstream signaling are main mechanisms of resistance to anti-HER2. More research in the clinical setting is needed to identify relevant resistance mechanisms. Abstract: Introduction: Despite promising results following targeted treatment with human epidermal growth factor receptor 2 (HER2)-inhibitors in HER2-positive gastric and esophageal adenocarcinoma (GEA), prognosis remains dismal. Many patients ultimately demonstrate progression following treatment due to resistance to HER2-targeted therapy. Here, we describe the potential primary and secondary resistance mechanisms to HER2-targeted therapy in GEA. Methods: We systematically searched PubMed/MEDLINE, EMBASE, and CENTRAL for eligible studies describing changes that were associated with drug resistance. Study quality was assessed using an adjusted version of the OHAT risk of bias tool. Quality of proposed resistance mechanisms was assessed using predefined criteria. Results: In total, 913 records were screened, of which 73 were included that investigated mechanisms of resistance against anti-HER2 treatment in cell lines, xenograft models, patient tissue samples, and publicly available datasets. HER2-targeted therapy resistance was found to be caused by HER2 receptor changes, upregulation of compensatory receptors, (re)activation of downstream signaling pathways like PI3K/AKT and MAPK, epithelial-to-mesenchymal transition, acquirement of stem cell-like properties, alterations in cell cycle related genes, cellular metabolism, and drug pharmacokinetics. Discussion: Several different mechanisms can contribute to drug resistance to anti-HER2 treatment in GEA, mainly through loss of or mutations in the HER2 receptor and upregulation of alternative receptors such as MET, HER3, and FGFRs. Despite these preclinical results, methods to overcome the proposed resistance mechanisms in the clinical setting are lacking. Therefore, further investigation of therapy resistance in GEA patients treated with HER2 targeted therapy is essential to overcome resistance and improve treatment outcome of these patients.